Political trauma and healing : biblical ethics for a postcolonial world - Brett, Mark G. (Grand Rapids, Michighan : William B. Eerdmans Publishing Company, 2016)
How can Scripture address the crucial justice issues of our time? In this book, Mark Brett offers a careful reading of biblical texts that speak to such pressing public issues as the legacies of colonialism, the demands of asylum seekers, the challenges of climate change, and the shaping of redemptive economies. Brett argues that the Hebrew Bible can be read as a series of reflections on political trauma and healing-- the long saga of successive ancient empires violently asserting their sovereignty over Israel and of the Israelites forced to live out new pathways toward restoration. Brett retrieves the prophetic voice of Scripture and applies it to our contemporary world, addressing current justice issues in a relevant, constructive, compelling manner." - from book blurb.
The ethics of conversation -- Limits and possibilities of secular theology -- Justice and postcolonial challenges -- Authors, imaginaries, and the ethics of interpretation -- Inner-biblical conversations -- Unfolding the national imaginary -- Sovereignty in the priestly tradition -- Isaiah, holiness, and justice -- Alternatives to the national tradition in Job -- Engaging the present -- Reconciliation and national sovereignties -- Undocumented immigrants, asylum seekers, and human rights -- Justice for the earth -- Economics and redemption.
Includes bibliographical references and indexes.
Print version record.
Keywords: Christianity and politics -- Biblical teaching; Christian ethics -- Biblical teaching; Australia -- Politics and government -- 21st century; Postcolonial theology; Christian ethics -- Biblical teaching; Christianity and politics -- Biblical teaching; Politics and government; Postcolonial theology; Australia; RELIGION / Christian Theology / Ethics; Electronic books